The effect of natural and biological pesticides on the degradation of synthetic pesticides - Paulina Książek-Trela; Ewa Szpyrka (Plant Protection Science, 2022)
Chemical plant protection methods have been used for decades. For some time now, society has paid attention to the hazards to human health resulting from the excessive use of chemical protection products. The presence of plant protection agent residues in crops causes changes in the natural environment, including biodiversity loss and the appearance of organisms harmful to plants, resistant to plant protection agents. To protect the health of humans, animals, and the environment, the principles of integrated plant protection have been introduced, giving priority to biological plant protection methods, for example, the use of biological active substances containing microorganisms (bacteria, yeasts, fungi) and natural substances. Microorganisms, as well as other natural substances, can accelerate the degradation of chemical plant protection products present in the environment and agricultural products. This review paper focuses on the effect of natural and biological pesticides on the degradation of synthetic pesticides. The most important and most perspective in integrated pest management (IPM) systems are Bacillus spp. and Trichoderma spp. because their effectiveness in pesticide degradation and the large number of commercial preparations containing these microorganisms available on the market. The application of biological pesticides recommended in IPM systems could significantly improve the quality of the soil, environment, and human health.